Effect of Heating Temperature on Indoor Photovoltaics - Dessy Ade Pratiwi; Andi Ibrahim Soumi; Wafiq Kurniawan (Engineering Proceedings)
The purpose of this research was to investigate the performance of photovoltaic modules when used in different heating temperatures. The heating temperature variants used were room T, TA = 50 °C, TB = 60 °C, and TC = 70 °C. The lamp capacity used was 5 watts with a bulb-type lamp. In addition, the circuit used was a series circuit. This research done on the effect of different temperatures of the heater placed under the photovoltaics showed that when there was an increase in the photovoltaic temperature, the voltage, current, power, and efficiency decreased. Therefore, it is necessary to limit the temperature used for photovoltaics.